A EFEKTIFITAS PEMBELAJARAN MICROTEACHING TERHADAP KEMAMPUAN KOMPETENSI CALON GURU - Rahmah, Mursidah; Rosyid, Abdul; Vonti, Lungguh Halira; Yani, Indri; Adela, Agnes (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
Teaching skills are one of the key indicators of pedagogical and professional competencies that pre-service teachers must possess. These skills include not only the ability to deliver subject matter but also the ability to manage learning activities, which consist of pre-activity, whilst-activity, and post-activity. This study aims to describe the effectiveness of microteaching learning in enhancing pre-service teachers' competencies. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings indicate that microteaching learning conducted over one semester provides adequate theoretical and practical preparation for pre-service teachers to undertake School Field Practice (PLP) 2. Students were able to design and implement lessons aligned with the applicable curriculum and effectively utilize appropriate teaching models and media. However, challenges remain in the development and implementation of lesson plans. Therefore, more intensive guidance from lecturers and mentor teachers is necessary to ensure that pre-service teachers are adequately prepared to teach effectively.